H The Hyperreality of Islamic Boarding School In The Romantic Comedic Soap Operas “Islamic Boarding School Rock N Dut” - Hasniar,; Ahmad Zulfikar Ali, (Advances in Humanities and Contemporary Studies, 2021)
Technology with seductive sophistication is considered a basic need that must be present at all times, one of which is television which can present programs that can change the mindset of every society. The reality that happens, television programs with various genres of films or soap operas do not reflect the realities that occur in the real world. For this reason, this article seeks to reveal the hyperreality that occurs in soap operas. As research with a semiotic approach, the primary data sources for this article are scenes from the Islamic boarding school rock n dut soap operas and research journals, and relevant books.